Economic freedom, good governance and the dynamics of development - Eva Medina; Vicente J. Montes-Gan (Journal of Applied Economics, 2018)
The purpose of this research is to provide empirical evidence about what institutions are most likely to favor development in its different stages. Firstly, we identify the three development stages that prevailed in the world between 1996 and 2011 according to the income classification of the World Bank corroborated with data from the UNDP Human Development Index. Secondly, we consider that a country had a "successful" behavior if it improved its development stage in that period. Grouping countries based on "success", instead of according to the income level, allows us to introduce the dynamics of development in the analysis. Thirdly, we formulate a panel data and a probit model to determine the institutions that are behind the success cases. The results identified economic freedom as the most important institution in all development stages; governance was also found essential, but only in the countries in the intermediate stage of development.
Keywords: 330; democracy; economic freedom; governance; growth regressions; Heterogeneity in cross-country analysis